Factor Afecting Good Governance on Performance Management - Junaid, Asriani; Suun, Muhammad; Nasaruddin, Fadliah (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to know the mediation influence of good university governance against the influence of organizational citizenship behavior (OCB) on the performance of religious-ideology-based university. The design of this research was an explanatory design. The research approach used was survey method, by giving questionnaires to respondents. The population in this research was religious-ideology-based private university in Makassar, while the research sample is the existing study program in each faculty, because study program is the heart of university which is the meeting place between stakeholders. Based on the results of this research, it can concluded that there is the significant direct influence between Organizational Citizenship Behavior against good university governnace and performance. The higher the Organizational Citizenship Behavior, the higher the good university governance and performance will be. The originality of this research is to test the mediation influenceof good university governance in collaboration with organizational citizenship behavior (OCB) variable and performance done at religious-ideology-based university in Indonesia which has different characteristics with universities in other regions.